Visual and Refractive Outcomes of a Toric Presbyopia-Correcting Intraocular Lens - Alice T. Epitropoulos (Journal of Ophthalmology)
Purpose. To evaluate outcomes in astigmatic patients implanted with the Trulign (Bausch + Lomb) toric presbyopia-correcting intraocular lens (IOL) during cataract surgery in a clinical practice setting. Methods. Retrospective study in 40 eyes (31 patients) that underwent cataract extraction and IOL implantation in a procedure using intraoperative wavefront aberrometry guidance (ORA system). Endpoints included uncorrected visual acuity (VA), reduction in refractive cylinder, accuracy to target, axis orientation, and safety. Results. At postoperative month 1, refractive cylinder was ≤0.50 D in 97.5% of eyes (≤1.00 D in 100%), uncorrected distance VA was 20/25 or better in 95%, uncorrected intermediate VA was 20/25 or better in 95%, and uncorrected near VA was 20/40 (J3 equivalent) or better in 92.5%. Manifest refraction spherical equivalent was within 1.00 D of target in 95% of eyes and within 0.50 D in 82.5%. Lens rotation was <5° and best-corrected VA was 20/25 or better in all eyes. Conclusion. The IOL effectively reduced refractive cylinder and provided excellent uncorrected distance and intermediate vision and functional near vision. Refractive predictability and rotational stability were exceptional. Implantation of this toric presbyopia-correcting IOL using ORA intraoperative aberrometry provides excellent refractive and visual outcomes in a standard of care setting.